Intelligent Multi-Area Power Control: Dynamic Knowledge Domain Inference Concept - Pandey R.K.; Gupta D.K. (My University, 2025)
This paper presents an intelligent multi-area power control with dynamic knowledge domain inference concept. The ongoing operational shift leads to unacceptable states variation, which may result in power oscillations, and if the controllers are not suitably designed, the system may be interactive and oscillations can aggravate. The study reports a new concept of updating control parameters, which is linked with operational shift, initially in an offline mode in building respective knowledge domain that fits into the framework of changing situations, to ensure states regulation. The proposed concept also provides flexibility to update the knowledge domain over and above offline data with newer dataset combining the nearest data clusters to derive an averaged data (controller parameter) within predefined boundary to change the controller functioning. The knowledge retrieval, as operational shift proceeds, has been mapped utilizing dynamical inference concept. The control so derived, effectively ensures the best damping well within time for the large network reliability and security. The structure of the controller so obtained is termed as the intelligent controller. In the present investigation, parameters of the respective controllers are stored in their respective knowledge domain on the modular basis. Firefly Algorithm (FA) with integral time multiplied by absolute error has been used as the objective function to be minimized. FA is then used to develop knowledge domain structure by way of deriving optimal controller parameters for corresponding operational shift to ensure oscillation damping with minimum settling time as well as overshoot/undershoot. The study is performed on six area sample power system. The proposed concept demonstrates an intelligent control concept for quick oscillation damping as the operating condition changes. Unified power flow controller has been used as an ancillary device as power system stabilizer approaches to the onset of unacceptable response. © 2017 IEEE.